Audiovisual Aesthetics of Sound and Movement in Contemporary Dance. (July 2020) - Howlin, Claire; Vicary, Staci; Orgs, Guido
How do movement and sound combine to produce an audiovisual aesthetics of dance? We assessed how audiovisual congruency influences continuous aesthetic and psychophysiological responses to contemporary dance. Two groups of spectators watched a recorded dance performance that included the performer's steps, breathing, and vocalizations but no music. Dance and sound were paired either as recorded or with the original soundtrack in reverse so that the performers' sounds were no longer coupled to their movements. A third group watched the dance video in silence. Audiovisual incongruency was rated as more enjoyable than congruent or silent conditions. In line with mainstream conceptions of dance as movement-to-music, arbitrary relationships between sound and movement were preferred to causal relationships in which performers produce their own soundtrack. Performed synchrony Granger caused changes in electrodermal activity only in the incongruent condition consistent with "aesthetic capture." Sound structures the perception of dance movement, increasing its aesthetic appeal.